Modulation of Hanle magnetoresistance in an ultrathin platinum film by ionic gating. (28th February 2023) - Maruyama, Yuu; Ohshima, Ryo; Shigematsu, Ei; Ando, Yuichiro; Shiraishi, Masashi
Abstract: Hanle magnetoresistance (HMR) is a type of magnetoresistance where interplay of the spin Hall effect, Hanle-type spin precession, and spin-dependent scattering at the top/bottom surfaces in a heavy metal controls the effect. In this study, we modulate HMR in ultrathin Pt by ionic gating, where the surface Rashba field created by a strong electric field at the interface between the ionic gate and Pt plays the dominant role in the modulation. This finding can facilitate investigations of gate-tunable, spin-related effects and fabrication of spin devices.